Prospects of BIPV in a typical residential building in Dhaka city - Sorower, Nur Jahan Beanta; Seum, Abu Niem; Raka, Rawnak Reza; Alvi, Md. Shifain Mahathir (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.